STUDY IMPLEMENTATION PLANNING GOODS PROPERTY/WEALTH OF THE UNIVERSITY OF PALANGKARAYA BY THE GOVERNMENT REGULATION OF THE REPUBLIK OF INDONESIA, NUMBER 6 IN, 2006 - Manya (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2024)
Research for this know implementation analysis the amount of goods and inventory possession / wealth countries and supporting factors and flexible in the inventory of goods in the possession of wealth University Palangk Raya. Research is carried out in the University of Palangka Raya elections this location the base behalf University of reasoning Palangka Raya is one of a University Charter filter biggest in Central Kalimantan and has attention in the aspects of inventory of goods possession / wealth Accordance with solicitation of reformasion.The analysis use of this data for research engineering analysis is done with all Network to review symptoms of various phenomena observed filter. For providing the closest description explains about the process of inventory management Consumer possession / wealth of the Regulations by the Government of Indonesia . Number 6 In 2006 about management possession of goods Country / Regional . The process of data analysis methods come with the base filter pioneer Nobody Miles and Huberman ( 1992 : 16 - 20 ) , with use of this Research engineering recruitment in one purposive sampling ( Sugiyono , 1998 : 58 ) that engineering trailer choose the closest - subject by subject behalf characteristics - characteristics or manifesting the population . Based on the results of the research found Upon your first policy implementation planning of goods possession of wealth in the United Kingdom University Palangkaraya still not yet get the optimal filter because several filter makes the point that the implementation of the control of the inventory of goods carried no Get one completely get the individual unit not yet to report accordance with terms , often not yet complete and not yet precise time. Second, organizations from tervoksi in the sub Supplies and unit filter helps in the implementation planning and support management products and related parties , with leave sample computer facilities and vehicles operational . flexible implementation planning BMN less able and less orderly administration of goods in inventory unit only partially work. Effect against the encrypted Supplies for do it one optimal activity. Catch problems available up to no funds in one specific budget or funds on a regular basis for planning activities to do it products.